HUBUNGAN PARITAS DENGAN BERAT BAYI LAHIR DI RUMAH SAKIT UMUM DAERAH DR. WAHIDIN SUDIRO HUSODO MOJOKERTO: RELATIONSHIP OF PARITY WITH BIRTH WEIGHT IN DR. WAHIDIN SUDIRO HUSODO MOJOKERTO - Wahyuningrum, Tria; Saudah, Noer; Novitasari, Widya Wahyu (Universitas Muhammadiyah Sidoarjo, 2015)
Maternal Mortality Rate and Infant Mortality Rate is indicator of the succes of health development. Infant is one indicator of a healthy newborn baby. There are many factors that effect, one of them is parity. Research design was used analytic correlation. The population were 128 respondents in a public hospital dr. Wahidin Sudiro Husodo since April to June 2015 using total samplin techniques. The independent variable was parity and the dependent variable was infant’s birth weight. The data were taken by retrospective data observasion patient’s medical records. The results of the crosstabulation used frequency distribution in spss 1.6 for windows parity with multiparity gave birth babies with low birth weight were 61 (76,3%), parity with primiparity gave birth babies with normal birth weight were 35 (74,5%) and parity with grandemultiparity gave birth babies with normal birth weight were 1 (0,8%). This research was used statistical test spearman rho test and result showed p = 0,00 <0,05 the H0 was rejected, which means there wasrelationship between parity and infant’s birth weight. Hopefully antenatal care can detect the risk of Low Birth Weight.